Computer-aided simulation of gas adsorption processes in nanopores; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Korchuganov A. V. Aleksandr; Zolnikov K. P. Konstantin; Kryzhevich D. S.; Grinyaev Yu. V.; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen